Desain Guard Adjust Pressure Tyre untuk Meminimalisir Dampak Ledakan Tyre di Departemen Plant PT. Hasta Panca Mandiri Utama Job Site OBI - Nanang Ari Setyowibowo; Nugroho Giga Pangestu; M. Bagus Panuntun (Malahayati Nursing Journal, 2024)
ABSTRACT The mining industry is a business sector with a high risk of accidents. The rapid use of heavy equipment, machines and the application of technology can pose potential dangers to the Mining and Environmental Safety (KPLH) aspect if mitigation is not carried out in each business process. To understand the design of the guard adjust pressure tire to minimize the impact of tire explosions in the Plant Department of PT. Hasta Panca Mandiri Utama Job Site OBI. The research method used was a descriptive study based on reliable literature sources. The use of guard adjust tire pressure is done by parking the unit according to the tools. The tire to be carried out for maintenance is placed directly above the tools/stepping on the tools. Next, the Log Out Tag Out (LOTO) mechanism is implemented by installing a block and activating LOTO on the unit. Mechanics can carry out tire pressure adjustment work through holes in the tools while remaining safe from the potential for the tire to explode. that adjusting activities have a big risk to workers due to the impact caused if the tire explodes. The use of guard adjust pressure tires can minimize the impact of explosions so that they do not hit the bodies of workers who are carrying out maintenance.  Keywords: Guard Adjust Pressure Tire Design, Tire Explosion Impact, Plant Department PT. Hasta Panca Mandiri Utama JOB SITE OBI  ABSTRAK Industri pertambangan merupakan sektor usaha dengan risiko tinggi terjadinya suatu kecelakaan. Penggunaan alat berat, mesin, dan penerapan teknologi yang pesat dapat menimbulkan potensi bahaya pada aspek Keselamatan Pertambangan dan Lingkungan Hidup (KPLH) apabila tidak dilakukan mitigasi pada setiap bisnis prosesnya.  Mengetahui desain guard adjust pressure tyre untuk meminimalisir dampak ledakan tyre tyre di Departemen Plant PT. Hasta Panca Mandiri Utama Job Site OBI. Metode penelitian yang dilakukan menggunakan studi deskriptif berdasarkan sumber literatur yang dapat dipertanggungjawabkan. Penggunaan guard adjust pressure tyre dilakukan dengan memarkirkan unit sesuai dengan tools. Tyre yang akan dilakukan maintenance ditempatkan tepat diatas tools/menginjak tools. Selanjutnya mekanisme Log Out Tag out (LOTO) diterapkan dengan pemasangan ganjal dan mengaktivkan LOTO pada unit. Mekanik dapat melakukan pekerjaan adjust pressure tyre melalui lubang pada tools dengan tetap aman dari potensi tyre yang meledak. Bahwa aktivitas adjust memiliki risiko yang besar kepada pekerja dikarenakan dampak yang ditimbulkan apabila tyre meledak. Penggunaan guard adjust pressure tyre dapat meminimalisir dampak ledakan sehingga tidak mengenai tubuh pekerja yang sedang melakukan maintenance. Kata Kunci: Desain Guard Adjust Pressure Tyre, Dampak Ledakan Tyre, Departemen Plant PT. Hasta Panca Mandiri Utama JOB SITE OBI